The Effect of Interpersonal Communication Via WhatsApp on Students' Socialization Ability - Eunike Chris Imanuela; Angelia Angelia; Dearma Purba (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2023)
This study explores how interpersonal communication responses in WhatsApp influence the social skills of FIKOM class 2021 students at Mercu Buana University Yogyakarta. With the prevalence of WhatsApp as a communication medium, its impact on social interactions and individual socialization becomes significant. The research aims to analyze the factors affecting perceptions and social skills in WhatsApp-mediated communication. A sample of 160 students was selected from a population of 266 students in the Faculty of Communication and Multimedia. The study utilized a quantitative approach with a questionnaire as the data collection tool, focusing on two variables: interpersonal communication responses (X) and student social skills (Y). Using SPSS software, the data analysis revealed that interpersonal communication responses accounted for 47.7% of the influence, while other factors constituted 52.3%. The findings highlight the considerable influence of interpersonal communication responses in WhatsApp on the development of social skills among students. This study contributes to understanding the relationship between digital communication behavior and its impact on socialization and social skills.